2018
DOI: 10.5604/01.3001.0011.5938
|View full text |Cite
|
Sign up to set email alerts
|

Vertical partial frontolateral laryngectomy with simultaneous pedunculated sternothyroid muscle flap reconstruction of the vocal fold – surgical procedure and treatment outcomes

Abstract: Vertical partial laryngectomy with or without pedunculated sternothyroid muscle flap reconstruction is a good method for the treatment of low- or intermediate-stage glottic cancer, especially when endoscopic access to the tumor is limited and when CO2 laser cannot be used. No significant functional disorders were observed in operated larynges.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…3D printing, provided that appropriate material similar to cartilage properties or cartilage itself is used as part of bioprinting, can be used in the future for larynx reconstruction after a partial laryngectomy. For some time now, autotransplants of tissue fragments taken from the patient in order to reconstruct the indispensable functions of the larynx have been used for these purposes [68]. Another problem is long defects in the trachea caused, among others, by tumour resections or traumas.…”
Section: D Printing In Reconstructionsmentioning
confidence: 99%
See 1 more Smart Citation
“…3D printing, provided that appropriate material similar to cartilage properties or cartilage itself is used as part of bioprinting, can be used in the future for larynx reconstruction after a partial laryngectomy. For some time now, autotransplants of tissue fragments taken from the patient in order to reconstruct the indispensable functions of the larynx have been used for these purposes [68]. Another problem is long defects in the trachea caused, among others, by tumour resections or traumas.…”
Section: D Printing In Reconstructionsmentioning
confidence: 99%
“…Interestingly, the animals who were implanted with a 360° round closed tube survived longer than those with a 270° open tube, theoretically more similar to real tracheal cartilage. Therefore, it is not an ideal method because, in the case of transplan-w celu odtworzenia lub zachowania niezbędnych funkcji krtani [68]. Osobnym problemem są długie ubytki tchawicy spowodowane m.in.…”
Section: D Printing In Reconstructionsmentioning
confidence: 99%
“…Moreover, swallowing and vocal functions can be restored in all patients without causing aspiration, and the tracheal tube can be withdrawn within 2-4 weeks after surgery in 90%-100% of patients. 8,14 However, whether voice quality differs following laryngeal defect repair with the RMF and PMF has rarely been studied.…”
Section: Introductionmentioning
confidence: 99%
“…Several clinical studies have shown that laryngeal defect repair with the RMF or PMF following vertical partial laryngectomy for patients with unilateral T2‐3 glottic carcinoma achieves a satisfactory recovery effect in terms of laryngeal function. Moreover, swallowing and vocal functions can be restored in all patients without causing aspiration, and the tracheal tube can be withdrawn within 2–4 weeks after surgery in 90%–100% of patients 8,14 . However, whether voice quality differs following laryngeal defect repair with the RMF and PMF has rarely been studied.…”
Section: Introductionmentioning
confidence: 99%